Application of Electronic Continuum Correction to Molecular Simulations of Nano/Bio Interfaces - Biriukov, Denys (Jihočeská univerzita, 2020)
Nowadays it is almost impossible to imagine our life without nanotechnologies. They are present in smartphones and many other gadgets we use every day, while advanced nanoparticle-based devises are currently indispensable in medicine, engineering, and science. In the case of biomedical applications, the knowledge how a specific nanomaterial behaves and changes its properties in complex physiological medium is essential to guarantee the accomplishment of all specific goals facing a scientist or engineer. Some of physical and chemical processes occurring when a nanodevice enters biological environment are yet very difficult to fully detail without accurate computer simulations, so special attention needs to be focused on theoretical studies of nano-bio interactions. In this thesis, molecular simulations were used to investigate the interactions between different nanomaterials (titanium dioxide, silicon dioxide, and gold) and aqueous solutions, which contain ions, organic molecules, and amino acids. The importance of this scope and particularly selected for this study materials and compounds is given in Introduction. To model nano/bio interfaces, we adopted and integrated recent theoretical approaches, which together with basic principles of molecular simulations are described in Methods. Obtained results are divided in four parts and address several important issues that are vital in deciphering molecular mechanisms, through which nanoparticles identify and bind various biomolecules. The simulation data are thoroughly discussed, compared to experiments, and used to explain some of experimental observations. Additionally, outcomes of this thesis serve as a springboard for further theoretical studies aimed to advance our understanding of nano-bio interactions.
Application of Electronic Continuum Correction to Molecular Simulations of Nano/Bio Interfaces
Keywords: solid/liquid interface; nanoparticles; molecular simulations; scaled charges; titania; silica; gold; aqueous solutions; ions; amino acids; adsorption; solid/liquid interface; nanoparticles; molecular simulations; scaled charges; titania; silica; gold; aqueous solutions; ions; amino acids; adsorption